Development of THGEM-based Detectors for Nuclear Fission Studies. Issue 1 (1st November 2022) - Bhattacharya, Purba; Sen, Arijit; Ghosh, Tilak Kumar; Majumdar, Nayana; Mukhopadhyay, Supratik
Abstract : To optimize the exploration of Super Heavy Elements (SHE), the key challenge is to understand the dynamics of the fusion-fission through the measurements of mass and angular distribution of the fission fragments. For the detection of fission fragments, position sensitive Multi-Wire Proportional Counters are generally used due to their high gain, good temporal and position resolution. However, these detectors use fragile anode wires having a diameter of only 10 μm and therefore they are vulnerable. In the present work, a detector based on robust Thick Gaseous Electron Multiplier (THGEM) has been proposed. A numerical demonstration of THGEM-Multi Wire hybrid detector technology as a possible candidate for the new generation low-energy fission studies and their evaluation as a function of different possible geometric and electric configuration in low-pressure gas is discussed here.